2004
DOI: 10.1038/sj.cgt.7700677
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of survivin expression by small interfering RNA reduces the clonogenic survival of human sarcoma cell lines independently of p53

Abstract: Survivin, a member of the inhibitors-of-apoptosis gene family, is overexpressed in many tumor types. Survivin is a prognostic marker of soft-tissue sarcomas, but the downregulation of survivin expression and the possible dependency of survivin downregulation on p53 in these tumors have not been investigated. Therefore, we applied small interfering RNA (siRNA) to knock down the expression of survivin in five human sarcoma cell lines with wild-type or mutant p53 alleles. Compared with survivin mRNA expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 45 publications
5
54
0
1
Order By: Relevance
“…[11][12][13][14] In a previous study, in five soft tissue sarcoma cell lines a reduced plating efficiency and occurrence of polyploidy independent of the p53 gene status was observed after treatment with survivin-specific siRNA. 15 This finding is in accordance with results of survivin knockdown experiments in other cancer cell lines. 5,[16][17][18][19][20] Furthermore, survivin overexpression was associated with radioresistance in tumor cell lines.…”
Section: Introductionsupporting
confidence: 90%
“…[11][12][13][14] In a previous study, in five soft tissue sarcoma cell lines a reduced plating efficiency and occurrence of polyploidy independent of the p53 gene status was observed after treatment with survivin-specific siRNA. 15 This finding is in accordance with results of survivin knockdown experiments in other cancer cell lines. 5,[16][17][18][19][20] Furthermore, survivin overexpression was associated with radioresistance in tumor cell lines.…”
Section: Introductionsupporting
confidence: 90%
“…Thus, at the time of irradiation, the cells were blocked in a more radiosensitive stage of the cell cycle. Kappler et al (22) have also recently shown a marked G 2 -M arrest, an impaired mitosis, and an increased number of polyploid cells after survivinspecific siRNA treatment in five human sarcoma cell lines. This is in line with our observations of a reduced cell viability in the MTT test (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits apoptosis (Altieri, 2001) and is involved in the spindle checkpoint and the regulation of proper chromosomal segregation during mitosis by acting as a member of the chromosomal passenger protein family (Li et al, 1998;Adams et al, 2001). A number of studies have demonstrated that the suppression of survivin results in cells with multipolar mitotic spindles that are either multinucleated or aneuploid (Li et al, 1999;Beltrami et al, 2004;Kappler et al, 2004). Some studies have also indicated that aneuploidy promotes chromosome instability (CIN) in glioma and cervical carcinoma cells (Nitta et al, 2002;Olaharski et al, 2006).…”
mentioning
confidence: 99%